Translating Evidence to Increase Quality and Dose of Upper Limb Therapy for Children with Unilateral Cerebral Palsy: A Pilot Study. (2nd July 2016) - Sakzewski, Leanne; Ziviani, Jenny; Boyd, Roslyn N.
ABSTRACT: Aims: To pilot efficacy of a tailored multifaceted implementation program to change clinical practice of occupational therapists (OTs) providing upper limb (UL) therapy for children with unilateral cerebral palsy (UCP). Methods: This before and after study piloted a multifaceted implementation program comprising audit/feedback, barrier identification, and education. Medical chart audits were conducted prior to and 12 months after the intervention. Primary process outcomes included proportion of children with UCP with (1) goals set; (2) goals measured; (3) received contemporary motor learning approach; (4) an adequate dose (30–40 hours); and (5) measured UL outcomes. Results: Three teams of OTs ( n = 9) participated. Forty-three audits at baseline and 53 at 12 months postimplementation program were conducted. Average time to complete audits was 10 min and four out of the five evidence criteria had complete data extracted from files. Changes in clinical behavior included greater measurement of goals before (+17%) and after (+22%) therapy; use of constraint therapy (+38%), bimanual therapy (+26%), home programs (+14%); measurement of UL outcomes before (+29%) and after (+23%) therapy. Children receiving the target dose increased from 0 to 10%. Conclusions: A tailored multifaceted implementation program was feasible to implement and led to meaningful changes in clinical practice behavior.